Hydrodynamic control of cadmium retention and bioaccumulation in a temperate estuary - Vibe Schourup-Kristensen; Janus Larsen; Martin M. Larsen; Jakob Strand; Lily-Jade Dupont; Ane Lopez de Gamiz Zearra; Gaia Grieco; Zhanna Tairova; Lindsey J. Broadus; Charlotte H. Clubley; Ange P. Ishimwe; Jesper Philip Aagaard Christensen; et al. (Marine Pollution Bulletin, 2026)

Effects of dietary fermented sugar kelp (Saccharina latissima) on intestinal histology, antioxidant capacity, and immune-related biomarkers of post-smolt Atlantic salmon (Salmo salar) - Sahar Sartipiyarahmadi; Ingvild Lunderød Øverbø; Benjamin Costas; Lourenço Ramos-Pinto; Nina S. Liland; Harald Sveier; Silje Steinsund; Tom Johnny Hansen; Øivind Strand; Jan Vidar Jakobsen; Antony J. Prabhu Philip; Sofie C. Remø (Fish & Shellfish Immunology, 2026)

Rock Salt Properties for Gas Storage in Mined Caverns: Part I–Short-Term Deformation and Yield, Long-Term Creep, and Gas Sealing Capacity - J. Sarout; M. Sari; L. Esteban; P. P. Mandal; J. Bourdet; D. Nguyen; J. Strand; E. Frery; L. Imbert; A. Francois; L. Langhi; D. Mallants (Rock Mechanics and Rock Engineering, 2026)
Deep rock salt formations can be drilled and solution-mined into caverns for permanent waste disposal, or temporary energy storage (natural gas/compressed air/hydrogen) to alleviate the intermittency of wind/solar energy. We report here the results of the laboratory appraisal of the key properties of a thick Devonian rock salt formation in the Canning Basin (Western Australia). Two representative but contrasting lithofacies were identified: a clean lithofacies made of nearly pure halite, and a dirty lithofacies comprising anhydrite, and dolomite/quartz inclusions. On each lithofacies, we conducted a mineralogical, microstructural and petrophysical characterisation, and a long-term four-stage triaxial test to simulate the impact of depth and anthropogenic stress perturbations. Strains and ultrasonic P-/S-wave velocities were monitored, and at specific stages of the triaxial test, long-term gas transmissivity and creep tests were conducted for up to 16 and 42 days, respectively. At all the triaxial stresses explored, including the in-situ conditions, the oven-dry clean salt facies exhibits a typical gas permeability of 5.10 –5 mD = 5.10 –20 m 2 , whereas the dirty salt is 100 to 1000 times more permeable to gas. The estimated steady-state creep rates are consistent with the extensive collection of literature data also reported here. The dominant creep mechanism is likely dislocation glide, complemented by frictional sliding where damage might exist. Pressure-solution creep is probably not dominant here, especially within the testing time scale. However, water is likely present in deep salt bodies and around man-made salt caverns, promoting overall creep through pressure-solution, and damage healing, hence reducing gas permeability even further.

Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Herbivory-Induced Nardus stricta Dominance Enriches Plant Silicon Relative to Phosphorus Enforcing Alternative Ecosystem Stable States in an Alpine Environment - G. N. Furey; G. Austrheim; L. T. Strand; J. Mulder; J. D. M. Speed; V. Martinsen (Ecosystems, 2026)
Herbivory can alter plant stoichiometry generating biogeochemical feedbacks that stabilize or drive transitions between ecosystem states. We report results after 23 years from a grazing experiment in Norway comparing five paired exclosures and grazed plots that were complemented with inclusion of five islands serving as a natural control. We tested the hypothesis that herbivory-driven shifts in plant dominance scale to alter elemental stocks and stoichiometry indicative of decelerated ecosystem biogeochemistry. Domestic sheep, Ovis aries , grazing was associated with dominance of the herbivory-resistant grass, Nardus stricta, rich in silicon (Si), while the ungrazed islands harbored a sheep-preferred grass Avenella flexuosa and forbs such as Solidago virgaurea relatively richer in phosphorus (P). Inside the exclosures, N. stricta had lower abundance than under grazing, but remained dominant at most sites. Its persistence suggests hysteresis on the trajectory to an ungrazed state displayed inside one mainland exclosure and on the islands. N. stricta had a high Si:P ratio, and through its dominance, this stoichiometry scaled to aboveground biomass with a more than doubling of the stock of Si (125%) on the mainland compared to the islands and a 46% increase in the concentration of Si. In contrast, the concentration of P in aboveground biomass on the islands was more than double (122%) the mainland. Herbivory appears to stabilize a high-Si ecosystem state compared to a high-P ungrazed state indicated through the plant Si:P ratio in this alpine ecosystem. This enrichment of silicon relative to phosphorus may cascade throughout the ecosystem with far-reaching implications.

Genome‐Wide Population Structure in a Marine Keystone Species, the European Flat Oyster ( Ostrea edulis ) - Homère J. Alves Monteiro; Dorte Bekkevold; George Pacheco; Stein Mortensen; Runyang Nicolas Lou; Nina O. Therkildsen; Arnaud Tanguy; Chloé Robert; Pierre De Wit; Dorte Meldrup; Ane T. Laugen; Philine S. E. zu Ermgassen; et al. (Molecular Ecology, 2025)
Ostrea edulis, the European flat oyster, was once a widespread economically and ecologically important marine species, but has suffered dramatic declines over the past two centuries. Consequently, there has been a surge in European restoration efforts, many of which focus on restocking as a conservation measure. In this study, we used whole‐genome sequencing (WGS) data to investigate the population structure, demographic history, and patterns of local adaptation of O. edulis across its natural distribution with increased sampling densities at Scandinavian localities. Results revealed seven distinct genetic clusters, including previously undescribed complex population structure in Norway, and evidence for introgression between genetic clusters in Scandinavia. We detected large structural variants (SVs) on three pseudo‐chromosomes. These megabase long regions were characterised by strong linkage disequilibrium and clear geographical differentiation, suggestive of chromosomal inversions potentially associated with local adaptation. The results indicated that genomic traces of past translocations of non‐native O. edulis were still present in some individuals, but overall, we found limited evidence of major impacts of translocations on the scale of contemporary population structure. Our findings highlight the importance of considering population structure and signatures of selection in the design of effective conservation strategies to preserve and restore wild native European flat oyster populations, and we provide direct knowledge safeguarding sustainable mitigation actions in this important species.

Piloting a culturally significant areas framework for spatial planning and management in the coastal environment of South Africa - Loyiso V. Dunga; Kerry J. Sink; Megan G. Van der Bank; Linda R. Harris; Lara Van Niekerk; Myriam Perschke; Ruan Brand; Judy Mann-Lang; Mike Bruton; Mia Strand; Nina Rivers; Stephen Lamberth; et al. (Marine Policy, 2025)

Multiple cryptic lineages and restricted gene flow in the decorator worm Diopatra Cuprea - Adam J. Ziegler; Tina M. Bell; Sarah K. Berke; Allan E. Strand; Erik E. Sotka (Marine Biology, 2025)
The decorator worm Diopatra cuprea Bosc, 1802 (Annelid; Polycheate; Onuphidae) is an ecosystem engineer within high-salinity estuaries of the southern and eastern United States. A previous study revealed five morphologically cryptic mitochondrial lineages across its broad geographic distribution. Here, we explore mitonuclear concordance of these lineages using single nucleotide polymorphisms (SNPs) genotyped with RADseq. We genotyped 3,162 SNPs from 233 D. cuprea and detected four deep lineages in the nuclear genome: a northern US clade (Massachusetts), a single nuclear clade within mid-Atlantic populations (i.e., Virginia south through northeastern Florida), a southeastern Florida clade, and a Gulf of Mexico clade. There was mitonuclear concordance within most individuals for three lineages, while two mitochondrial lineages were detected in a single mid-Atlantic nuclear lineage. Thus, there appear to be four cryptic lineages of D. cuprea that suggest four distinct species that rarely hybridize. Within the mid-Atlantic lineage, we detected increasing genetic isolation of populations with increasing geographic distance, a pattern consistent with low dispersal of D. cuprea larvae. Cryptic diversity within the D. cuprea complex is consistent with other common and geographically widespread annelid and Diopatra species that are now being revealed using high-throughput sequencing.

Ocean equity: from assessment to action to improve social equity in ocean governance - Nathan J. Bennett; Veronica Relano; Katina Roumbedakis; Jessica Blythe; Mark Andrachuk; Joachim Claudet; Neil Dawson; David Gill; Natali Lazzari; Shauna L. Mahajan; Ella-Kari Muhl; Maraja Riechers; et al. (Frontiers in Marine Science, 2025)
Inequity is ubiquitous in the ocean, and social equity receives insufficient attention in ocean governance and management efforts. Thus, we assert that proponents of sustainability must center social equity in future ocean governance, to address past social and environmental injustices, to align with international law and conservation policy, and to realize objectives of sustainability. This obligation applies across all marine policy realms, including marine conservation, fisheries management, climate adaptation and the ocean economy, in all socio-political contexts and at different geographical scales. Indeed, many governmental, non-governmental, and philanthropic organizations are striving to advance social equity across their ocean sustainability focused agendas, policies, programs, initiatives, and portfolios. To date, however, there has been limited attention to how to meaningfully assess status and monitor progress on social equity in ocean governance (aka “ocean equity”) across different marine policy realms. Here, we contribute to ongoing efforts to advance ocean equity through providing guidance on five steps to develop bespoke, fit to purpose and contextually appropriate assessment and monitoring frameworks and approaches to measure status of and track changes in ocean equity. These steps include: 1) Clearly articulating the overarching purpose and aim; 2) Convening a participatory group and process to co-design the assessment framework; 3) Identifying important objectives, aspects and attributes of social equity to assess; 4) Selecting and developing indicators, methods, and measures; and 5) Collecting, analyzing and evaluating data. Then, we discuss four subsequent steps to take into account to ensure that assessments lead to adaptations or transformations to improve ocean equity. These steps include: 1) Communicating results to reach key audiences, to enable learning and inform decision-making; 2) Deliberating on actions and selecting interventions to improve ocean equity; 3) Ensuring actions to improve ocean equity are implemented; and, 4) Committing to continual cycles of monitoring, evaluation, learning and adapting at regular intervals. Following these steps could contribute to a change in how oceans are governed. The diligent pursuit of ocean equity will help to ensure that the course towards a sustainable ocean is more representative, inclusive and just.

P25-12 Effects of personalized chemical mixture on endocrine disruption based on estrogen nuclear receptors - L. Reis; D. Strand; B. Lundgren; J. Martin; O. Karlsson (Toxicology Letters, 2024)

Evaluating the contribution of plant metabolic pathways in the light to the ATP:NADPH demand using a meta-analysis of isotopically non-stationary metabolic flux analyses - Kaila Smith; Deserah D. Strand; Berkley J. Walker (Photosynthesis Research, 2024)
Balancing the ATP: NADPH demand from plant metabolism with supply from photosynthesis is essential for preventing photodamage and operating efficiently, so understanding its drivers is important for integrating metabolism with the light reactions of photosynthesis and for bioengineering efforts that may radically change this demand. It is often assumed that the C3 cycle and photorespiration consume the largest amount of ATP and reductant in illuminated leaves and as a result mostly determine the ATP: NADPH demand. However, the quantitative extent to which other energy consuming metabolic processes contribute in large ways to overall ATP: NADPH demand remains unknown. Here, we used the metabolic flux networks of numerous recently published isotopically non-stationary metabolic flux analyses (INST-MFA) to evaluate flux through the C3 cycle, photorespiration, the oxidative pentose phosphate pathway, the tricarboxylic acid cycle, and starch/sucrose synthesis and characterize broad trends in the demand of energy across different pathways and compartments as well as in the overall ATP:NADPH demand. These data sets include a variety of species including Arabidopsis thaliana , Nicotiana tabacum , and Camelina sativa as well as varying environmental factors including high/low light, day length, and photorespiratory levels. Examining these datasets in aggregate reveals that ultimately the bulk of the energy flux occurred in the C3 cycle and photorespiration, however, the energy demand from these pathways did not determine the ATP: NADPH demand alone. Instead, a notable contribution was revealed from starch and sucrose synthesis which might counterbalance photorespiratory demand and result in fewer adjustments in mechanisms which balance the ATP deficit.

Reflections on the past, present, and potential futures of knowledge hierarchies in ocean biodiversity governance research - Holly J. Niner; David Wilson; Kelly Hoareau; Mia Strand; Jennifer Whittingham; Dylan McGarry; Bolanle Erinosho; Sulley Ibrahim; Sirkka Tshiningayamwe; Senia Febrica; Alana Malinde S. N. Lancaster; Milica Prokic (Frontiers in Marine Science, 2024)
Governance of the ocean and its biodiversity is deeply entangled within social, political and cultural histories. The evolution of marine science has been subject to similar influences, and we (the authors) consider these factors to create, embed and reinforce knowledge hierarchies in ocean governance processes and associated research that set societal patterns of prioritisation and exclusion. Such knowledge hierarchies have constructed dominant Western-oriented knowledge systems as ‘rational’ and ‘objective’ approaches to environmental governance in contrast to non-Western knowledge systems and have led to a dominance of natural (normal) sciences over centralised biodiversity governance. The extraction and incorporation of traditional knowledge into the Western-oriented scientific canon through myriad historical and contemporary processes in ocean biodiversity governance often reproduce knowledge hierarchies, do not benefit knowledge holders and are often considered incomplete, inappropriate or absent. As we address current ocean biodiversity and conservation challenges, researchers must be aware of the history of knowledge extraction, impositions and assumptions within their fields. Researchers must also actively acknowledge and address these histories in their work to avoid marginalisation and support ethical, empathetic, and rigorous knowledge production that meets the needs of society. In this paper, through a development of the concept of knowledge hierarchies, we explore case studies of research diverse in geography and discipline ranging from action research in Namibia, the application of arts-based methodologies in legal proceedings to research focused at an international level, and the concept of ocean literacies, all of which are located under the umbrella of a project specifically targeting transformative ocean governance. It becomes evident that knowledge hierarchies are multi-layered, perpetuating, and often reproduced even when attempting to address hierarchies through such methods as the integration or ‘bringing together’ of diverse knowledge systems. Effective change will therefore require sensitive and multi-faceted approaches to knowledge hierarchies, including processes of embracing discomfort, which will be important to work with, as well as through. While there will be continued tensions between hierarchies, it is a sine qua non that researchers need to build a commitment to understanding where powers lie, rather than ignoring such imbalances or, similarly, by idealising approaches.

Contribution of VLF electromagnetic survey to the investigation of Hessdalen lights (Norway) - G.N. Vargemezis; J. Zlotnicki; B.G. Hauge; A.L. Kjøniksen; E.P. Strand (Journal of Applied Geophysics, 2024)

Blue mussel (Mytilus edulis) silage, a possible low trophic marine protein source for Atlantic salmon (Salmo salar L.) - Sahar Sartipiyarahmadi; Antony J. Prabhu Philip; Aksel N. Forshei; Harald Sveier; Silje Steinsund; Malin Kleppe; Erik-Jan Lock; Angelico Madaro; Tom Johnny Hansen; Øivind Strand; Martin Wiech; Jan Vidar Jakobsen; et al. (Aquaculture, 2024)

Capacity of community health centers to treat snakebite envenoming in indigenous territories of the Brazilian Amazon - André Sachett; Eleanor Strand; Thiago Serrão-Pinto; Alexandre da Silva Neto; Thais Pinto Nascimento; Sewbert Rodrigues Jati; Gisele dos Santos Rocha; Sediel Ambrósio Andrade; Fan Hui Wen; Manuela Berto Pucca; João Vissoci; Charles J. Gerardo; et al. (Toxicon, 2024)

Comparative Description and Analysis of Oyster Aquaculture in Selected Atlantic Regions: Production, Market Dynamics, and Consumption Patterns - Johannes A. Iitembu; Daniel Fitzgerald; Themistoklis Altintzoglou; Pierre Boudry; Peter Britz; Carrie J. Byron; Daniel Delago; Sophie Girard; Colin Hannon; Marcia Kafensztok; Francisco Lagreze; Jefferson Francisco Alves Legat; et al. (Fishes, 2023)
In the face of an increasing world population and a subsequent need for an increase in sustainable and healthy food production, low trophic species, such as oysters, emerge as a promising alternative. However, regional variations in oyster production techniques, market dynamics, and consumption patterns create challenges for both the global and local industry’s growth. In this study, a descriptive qualitative analysis of oyster markets across seven Atlantic regions was carried out. The Pacific oyster (Crassostrea gigas) was found to be farmed in most Atlantic regions except the US but is classified as invasive in Sweden and potentially invasive in South Africa. Other farmed and/or harvested species include native species (C. gasar and C. rhizophorae) in Brazil, the American cupped oyster (C. virginica) in the US, and the European flat oyster (Ostrea edulis) in France, Sweden, and the US. In Irish farms, Pacific oysters are primarily for export to European markets. The marine aquaculture sectors of Sweden, South Africa, and Namibia, as well as Brazil’s farming for C. gasar, were found to be underdeveloped. This study also observed a variation in licensing, property rights, and regulatory frameworks. Financial challenges for small businesses, ecological implications of seed production techniques, biosecurity risks, and public health considerations are emphasized as critical areas for attention. This study offers valuable insights into the selected markets and can serve as a useful resource for policymakers, aquaculture practitioners, and stakeholders in optimizing global shellfish industry strategies.

Improved separation and quantification method for microplastic analysis in sediment: A fine-grained matrix from Arctic Greenland - K.B. Parga Martínez; V.H. da Silva; T.J. Andersen; N.R. Posth; J. Strand (Marine Pollution Bulletin, 2023)

A two way process – Social capacity as a driver and outcome of equitable marine spatial planning - Céline Jacob; Sereno DuPrey Diederichsen; Liam Fullbrook; Amanda T. Lombard; Siân E. Rees; Nina Rivers; Bernadette Snow; Mia Strand; Rachel Zuercher; Holly J. Niner (Marine Policy, 2023)

Tradeoffs and synergies in wetland multifunctionality: A scaling issue - P.A. Hambäck; L. Dawson; P. Geranmayeh; J. Jarsjö; I. Kačergytė; M. Peacock; D. Collentine; G. Destouni; M. Futter; G. Hugelius; S. Hedman; S. Jonsson; et al. (Science of The Total Environment, 2023)

Latitudinally distinct stocks of Atlantic cod face fundamentally different biophysical challenges under on‐going climate change - Olav Sigurd Kjesbu; Maud Alix; Anne Britt Sandø; Espen Strand; Peter J. Wright; David G. Johns; Anders Thorsen; C. Tara Marshall; Kjell Gunnar Bakkeplass; Frode B. Vikebø; Mari Skuggedal Myksvoll; Geir Ottersen; et al. (Fish and Fisheries, 2023)
The reproductive success of marine ectotherms is especially vulnerable in warming oceans due to alterations in adult physiology, as well as embryonic and larval survival prospects. These vital responses may, however, differ considerably across the species' geographical distribution. Here we investigated the life history, focusing on reproductive ecology, of three spatially distant populations (stocks) of Atlantic cod ( Gadus morhua , Gadidae) (50–80° N), in the Irish/Celtic Seas‐English Channel Complex, North and Barents Seas, under past and projected climate. First, experimental tracking of spawning behaviour evidenced that the ovulation cycle is highly distressed at ≥9.6 (±0.25)°C ( T up ). This knife‐edge threshold resulted in erratic spawning frequencies, whereas vitellogenin sequestration remained unaffected, indicating endocrine rather than aerobic scope constraints. Cod in the Celtic Sea‐English Channel are, therefore, expected to show critical stock depensation over the next decades as spawning grounds warm above T up , with Irish Sea cod subsequently at risk. Second, in the relatively cooler North Sea, the northward retraction of Calanus finmarchicus (Calanidae) and Para‐Pseudocalanus spp. (Clausocalanidae) (1958–2017) limit cod larvae feeding opportunities, particularly in the southernmost subarea. However, the contrasting increase in Calanus helgolandicus (Calanidae) does not counteract this negative effect, likely because cod larvae hatch ahead of its abundance peaks. Overfishing again comes as a twin effect. Third, in the still relatively cold Barents Sea, the sustainably harvested cod benefit from improved food conditions in the recent ice‐free polar region but at the energetic cost of lengthier and faster spawning migrations. Consequently, under climate change local stocks are stressed by different mechanistic factors of varying management severity.

Cardiomyocyte-specific overexpression of syndecan-4 in mice results in activation of calcineurin-NFAT signalling and exacerbated cardiac hypertrophy - Ida G. Lunde; J. Magnus Aronsen; A. Olav Melleby; Mari E. Strand; Jonas Skogestad; Bård A. Bendiksen; M. Shakil Ahmed; Ivar Sjaastad; Håvard Attramadal; Cathrine R. Carlson; Geir Christensen (Molecular Biology Reports, 2022)
Background Cardiomyocyte hypertrophy is a hallmark of cardiac dysfunction in patients with aortic stenosis (AS), and can be triggered by left ventricular (LV) pressure overload in mice by aortic banding (AB). Syndecan-4 is a transmembrane heparan sulphate proteoglycan which is found increased in the myocardium of AS patients and AB mice. The role of syndecan-4 in cardiomyocyte hypertrophy is not well understood. Purpose of the study We developed mice with cardiomyocyte-specific overexpression of syndecan-4 ( Sdc4-Tg ) and subjected these to AB to examine the role of syndecan-4 in hypertrophy and activation of the pro-hypertrophic calcineurin-NFAT signalling pathway. Methods and results Sdc4-Tg mice showed exacerbated cardiac remodelling upon AB compared to wild type (WT). At 2–6 weeks post-AB, Sdc4-Tg and WT mice showed similar hypertrophic growth, while at 20 weeks post-AB, exacerbated hypertrophy and dysfunction were evident in Sdc4-Tg mice. After cross-breeding of Sdc4-Tg mice with NFAT-luciferase reporter mice, we found increased NFAT activation in Sdc4-Tg hearts after AB. Immunoprecipitation showed that calcineurin bound to syndecan-4 in Sdc4-Tg hearts. Isolated cardiomyocytes from Sdc4-Tg mice showed alterations in Ca 2+ fluxes, suggesting that syndecan-4 regulated Ca 2+ levels, and thereby, activating the syndecan-4-calcineurin complex resulting in NFAT activation and hypertrophic growth. Similarly, primary cardiomyocyte cultures from neonatal rats showed increased calcineurin-NFAT-dependent hypertrophic growth upon viral Sdc4 overexpression. Conclusion Our study of mice with cardiomyocyte-specific overexpression of Sdc4 have revealed that syndecan-4 is important for activation of the Ca 2+ -dependent calcineurin-NFAT signalling pathway, hypertrophic remodelling and dysfunction in cardiomyocytes in response to pressure overload.

Effect of Mytilus coruscus selective filtration on phytoplankton assemblages - Tao Jiang; Huizhu Pan; Laura Steeves; Zengjie Jiang; Ramón Filgueira; Øivind Strand; Tore Strohmeier; Peter J. Cranford; Zhengguo Cui (Frontiers in Marine Science, 2022)
The feeding selectivity of bivalves can play an important role in shaping the structure of phytoplankton communities of natural waters. This could be particularly true in waters with intensive bivalves farming, like Sungo Bay, Northern China. Understanding the role of bivalve feeding behavior is important for assessing how the dense cultivation of bivalves may affect phytoplankton community composition and food web structure in farm areas. In this study, we investigated the feeding selectivity of blue mussel Mytilus coruscus on natural phytoplankton assemblages in Sungo Bay using both optical microscopy and HPLC-pigment analysis. Results showed that cryptophytes dominated the phytoplankton community and made up 66.1% of the total phytoplankton abundance. A comparison of phytoplankton composition between natural and filtered seawater showed that M. coruscus preferred cryptophytes and dinoflagellates than Chaetoceros spp. and Skeletonema spp. Cryptophytes were not detected in gut contents by microscopic observation, while their marker pigment alloxanthin was present, suggesting they were also consumed by M. coruscus and can be readily digested. This highlights the shortcomings of microscopic methods and the significance of HPLC-pigment analysis in obtaining a comprehensive understanding of feeding selectivity of bivalves. The proportions of Chaetoceros spp. and Skeletonema spp. in gut contents were significantly lower than their proportions in the seawater, and contrastingly, the proportions of Cocconeis spp. and Pinnularia spp. showed opposite patterns. The marker pigments prasinoxanthin and zeaxanthin were detected in the gut of M. coruscus indicating that picophytoplankton (e.g., prasinophytes and Synechococcus ) are also food sources for this bivalve. This information furthers our understanding of bivalve aquaculture and environment interactions.

qPCR screening for Yersinia ruckeri clonal complex 1 against a background of putatively avirulent strains in Norwegian aquaculture - Andreas Riborg; Snorre Gulla; David Strand; Jannicke Wiik‐Nielsen; Anita Rønneseth; Timothy J. Welch; Bjørn Spilsberg; Duncan J. Colquhoun (Journal of Fish Diseases, 2022)
Although a number of genetically diverse Yersinia ruckeri strains are present in Norwegian aquaculture environments, most if not all outbreaks of yersiniosis in Atlantic salmon in Norway are associated with a single specific genetic lineage of serotype O1, termed clonal complex 1. To investigate the presence and spread of virulent and putatively avirulent strains in Norwegian salmon farms, PCR assays specific for Y. ruckeri (species level) and Y. ruckeri clonal complex 1 were developed. Following extensive screening of water and biofilm, the widespread prevalence of putatively avirulent Y. ruckeri strains was confirmed in freshwater salmon hatcheries, while Y. ruckeri clonal complex 1 was found in fewer farms. The formalin‐killed bacterin yersiniosis vaccine was detected in environmental samples by both PCR assays for several weeks post‐vaccination. It is thus important to interpret results from recently vaccinated fish with great care. Moreover, field studies and laboratory trials confirmed that stressful management procedures may result in increased shedding of Y. ruckeri by sub‐clinically infected fish. Analysis of sea water sampled throughout thermal delousing procedures proved effective for detection of Y. ruckeri in sub‐clinically infected populations.

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Body size and digestive system shape resource selection by ungulates: A cross‐taxa test of the forage maturation hypothesis - Saeideh Esmaeili; Brett R. Jesmer; Shannon E. Albeke; Ellen O. Aikens; Kathryn A. Schoenecker; Sarah R. B. King; Briana Abrahms; Bayarbaatar Buuveibaatar; Jeffrey L. Beck; Randall B. Boone; Francesca Cagnacci; Simon Chamaillé‐Jammes; et al. (Ecology Letters, 2021)
The forage maturation hypothesis (FMH) states that energy intake for ungulates is maximised when forage biomass is at intermediate levels. Nevertheless, metabolic allometry and different digestive systems suggest that resource selection should vary across ungulate species. By combining GPS relocations with remotely sensed data on forage characteristics and surface water, we quantified the effect of body size and digestive system in determining movements of 30 populations of hindgut fermenters (equids) and ruminants across biomes. Selection for intermediate forage biomass was negatively related to body size, regardless of digestive system. Selection for proximity to surface water was stronger for equids relative to ruminants, regardless of body size. To be more generalisable, we suggest that the FMH explicitly incorporate contingencies in body size and digestive system, with small‐bodied ruminants selecting more strongly for potential energy intake, and hindgut fermenters selecting more strongly for surface water.

Founder effects shape linkage disequilibrium and genomic diversity of a partially clonal invader - Ben A. Flanagan; Stacy A. Krueger‐Hadfield; Courtney J. Murren; Chris C. Nice; Allan E. Strand; Erik E. Sotka (Molecular Ecology, 2021)
The genomic variation of an invasive species may be affected by complex demographic histories and evolutionary changes during the invasion. Here, we describe the relative influence of bottlenecks, clonality, and population expansion in determining genomic variability of the widespread red macroalga Agarophyton vermiculophyllum . Its introduction from mainland Japan to the estuaries of North America and Europe coincided with shifts from predominantly sexual to partially clonal reproduction and rapid adaptive evolution. A survey of 62,285 SNPs for 351 individuals from 35 populations, aligned to 24 chromosome‐length scaffolds indicate that linkage disequilibrium (LD), observed heterozygosity ( H o ), Tajima's D, and nucleotide diversity (Pi) were greater among non‐native than native populations. Evolutionary simulations indicate LD and Tajima's D were consistent with a severe population bottleneck. Also, the increased rate of clonal reproduction in the non‐native range could not have produced the observed patterns by itself but may have magnified the bottleneck effect on LD. Elevated marker diversity in the genetic source populations could have contributed to the increased H o and Pi observed in the non‐native range. We refined the previous invasion source region to a ~50 km section of northeastern Honshu Island. Outlier detection methods failed to reveal any consistently differentiated loci shared among invaded regions, probably because of the complex A. vermiculophyllum demographic history. Our results reinforce the importance of demographic history, specifically founder effects, in driving genomic variation of invasive populations, even when localized adaptive evolution and reproductive system shifts are observed.

Explaining the worldwide distributions of two highly mobile species: Cakile edentula and Cakile maritima - Elliot C. Shaw; Rachael Fowler; Sara Ohadi; Michael J. Bayly; Rosemary A. Barrett; Josquin Tibbits; Allan Strand; Charles G. Willis; Kathleen Donohue; Philipp Robeck; Roger D. Cousens (Journal of Biogeography, 2021)
Aim If we are able to determine the geographic origin of an invasion, as well as its known area of introduction, we can better appreciate the innate environmental tolerance of a species and the strength of selection for adaptation that colonizing populations have undergone. It also enables us to maximize the success of searches for effective biological control agents. We determined the number of successful colonization events that have occurred throughout the world for two Cakile species and compared the climates from which they originated, in which they established and then spread. Location Worldwide. Taxon Sea‐Rockets ( Cakile spp.), Brassicaceae. Methods We used a high‐throughput sequencing and a genome skimming approach combined with Bayesian Inference phylogenetics to examine variation in entire chloroplast genomes and regions of nuclear ribosomal DNA within native and introduced areas. Databases were used to compare climates between native ranges and introduced regions for multiple clades within each species. Results At least seven clades have invaded different regions of the world. In most cases we were able to identify their source regions and climates. The environmental bottlenecks differed in intensity: while some clades colonized into climates that were similar to climates in their native range, other clades had a very broad innate environmental tolerance such that new invasions succeeded beyond the climate range of native populations. We found clear evidence of hybridization—specifically, chloroplast capture—between two species in Australia. Conclusions Results here show that these species are sometimes capable of colonizing in climates that are beyond the climate range of native populations. Whether successful colonization beyond native climate niches requires de novo adaptation, or whether it represents an innate broad fundamental niche requires further investigation. Cakile species provide an excellent opportunity to study replicated climate adaptation trajectories.

Disrupting the disruptors: the consequences of mutations in mobile elements for ecologically important life history traits - Matthew T. Rutter; April M. Bisner; Clare Kohler; Keyaira Morgan; Olivia Musselman; Julia Pickel; Jerica Tan; Yuki Yamasaki; Jay Willson; Hilary S. Callahan; Allan E. Strand; Courtney J. Murren (Evolutionary Ecology, 2020)

When and where plant‐soil feedback may promote plant coexistence: a meta‐analysis - Kerri M. Crawford; Jonathan T. Bauer; Liza S. Comita; Maarten B. Eppinga; Daniel J. Johnson; Scott A. Mangan; Simon A. Queenborough; Allan E. Strand; Katharine N. Suding; James Umbanhowar; James D. Bever (Ecology Letters, 2019)
Plant‐soil feedback (PSF) theory provides a powerful framework for understanding plant dynamics by integrating growth assays into predictions of whether soil communities stabilise plant–plant interactions. However, we lack a comprehensive view of the likelihood of feedback‐driven coexistence, partly because of a failure to analyse pairwise PSF, the metric directly linked to plant species coexistence. Here, we determine the relative importance of plant evolutionary history, traits, and environmental factors for coexistence through PSF using a meta‐analysis of 1038 pairwise PSF measures. Consistent with eco‐evolutionary predictions, feedback is more likely to mediate coexistence for pairs of plant species (1) associating with similar guilds of mycorrhizal fungi, (2) of increasing phylogenetic distance, and (3) interacting with native microbes. We also found evidence for a primary role of pathogens in feedback‐mediated coexistence. By combining results over several independent studies, our results confirm that PSF may play a key role in plant species coexistence, species invasion, and the phylogenetic diversification of plant communities.

Forecasting the genetic influences of red drum stock enhancement in South Carolina - Christopher J. Katalinas; John D. Robinson; Allan E. Strand; Tanya Darden; Karl Brenkert; Michael R. Denson (Fisheries Management and Ecology, 2019)
The South Carolina Department of Natural Resources ( SCDNR ) began stocking red drum, Sciaenops ocellatus (Linnaeus), in 1989 to augment the abundance of juveniles available for recreational harvest in South Carolina estuaries. While stock enhancement can help supplement wild populations under high fishing pressure, releasing hatchery‐raised fish into the wild also presents the risk of decreased genetic diversity. An individual‐based model ( IBM ) was developed to forecast the genetic influences of stocking on the wild spawning population to inform responsible stocking strategies. Model results indicated the SCDNR red drum stock enhancement programme should maintain mean contributions of stocked fish no greater than 30% per year class over a 45‐year stocking period, coupled with at least 10 effective breeders in the hatchery replaced annually, to maintain current levels of genetic diversity estimated in the wild population. The IBM is a useful tool for hatchery managers to guide responsible stock enhancement.

Attraction and repulsion of mobile wild organisms to finfish and shellfish aquaculture: a review - Myriam D. Callier; Carrie J. Byron; David A. Bengtson; Peter J. Cranford; Stephen F. Cross; Ulfert Focken; Henrice M. Jansen; Pauline Kamermans; Anders Kiessling; Thomas Landry; Francis O'Beirn; Erik Petersson; et al. (Reviews in Aquaculture, 2018)
Knowledge of aquaculture–environment interactions is essential for the development of a sustainable aquaculture industry and efficient marine spatial planning. The effects of fish and shellfish farming on sessile wild populations, particularly infauna, have been studied intensively. Mobile fauna, including crustaceans, fish, birds and marine mammals, also interact with aquaculture operations, but the interactions are more complex and these animals may be attracted to (attraction) or show an aversion to (repulsion) farm operations with various degrees of effects. This review outlines the main mechanisms and effects of attraction and repulsion of wild animals to/from marine finfish cage and bivalve aquaculture, with a focus on effects on fisheries‐related species. Effects considered in this review include those related to the provision of physical structure (farm infrastructure acting as fish aggregating devices ( FAD s) or artificial reefs ( AR s), the provision of food (e.g. farmed animals, waste feed and faeces, fouling organisms associated with farm structures) and some farm activities (e.g. boating, cleaning). The reviews show that the distribution of mobile organisms associated with farming structures varies over various spatial (vertical and horizontal) and temporal scales (season, feeding time, day/night period). Attraction/repulsion mechanisms have a variety of direct and indirect effects on wild organisms at the level of individuals and populations and may have implication for the management of fisheries species and the ecosystem in the context of marine spatial planning. This review revealed considerable uncertainties regarding the long‐term and ecosystem‐wide consequences of these interactions. The use of modelling may help better understand consequences, but long‐term studies are necessary to better elucidate effects.

Lessons from the First Generation of Marine Ecological Forecast Products - Mark R. Payne; Alistair J. Hobday; Brian R. MacKenzie; Desiree Tommasi; Danielle P. Dempsey; Sascha M. M. Fässler; Alan C. Haynie; Rubao Ji; Gang Liu; Patrick D. Lynch; Daniela Matei; Anna K. Miesner; et al. (Frontiers in Marine Science, 2017)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Invasion of novel habitats uncouples haplo‐diplontic life cycles - Stacy A. Krueger‐Hadfield; Nicole M. Kollars; James E. Byers; Thomas W. Greig; Mareike Hammann; David C. Murray; Courtney J. Murren; Allan E. Strand; Ryuta Terada; Florian Weinberger; Erik E. Sotka (Molecular Ecology, 2016)
Baker's Law predicts uniparental reproduction will facilitate colonization success in novel habitats. While evidence supports this prediction among colonizing plants and animals, few studies have investigated shifts in reproductive mode in haplo‐diplontic species in which both prolonged haploid and diploid stages separate meiosis and fertilization in time and space. Due to this separation, asexual reproduction can yield the dominance of one of the ploidy stages in colonizing populations. We tested for shifts in ploidy and reproductive mode across native and introduced populations of the red seaweed Gracilaria vermiculophylla . Native populations in the northwest Pacific Ocean were nearly always attached by holdfasts to hard substrata and, as is characteristic of the genus, haploid–diploid ratios were slightly diploid‐biased. In contrast, along North American and European coastlines, introduced populations nearly always floated atop soft‐sediment mudflats and were overwhelmingly dominated by diploid thalli without holdfasts. Introduced populations exhibited population genetic signals consistent with extensive vegetative fragmentation, while native populations did not. Thus, the ecological shift from attached to unattached thalli, ostensibly necessitated by the invasion of soft‐sediment habitats, correlated with shifts from sexual to asexual reproduction and slight to strong diploid bias. We extend Baker's Law by predicting other colonizing haplo‐diplontic species will show similar increases in asexuality that correlate with the dominance of one ploidy stage. Labile mating systems likely facilitate colonization success and subsequent range expansion, but for haplo‐diplontic species, the long‐term eco‐evolutionary impacts will depend on which ploidy stage is lost and the degree to which asexual reproduction is canalized.

A first report on coexistence and hybridization of Mytilus trossulus and M. edulis mussels in Greenland - R. Wenne; L. Bach; M. Zbawicka; J. Strand; J. H. McDonald (Polar Biology, 2016)

Irisin and FNDC5: effects of 12-week strength training, and relations to muscle phenotype and body mass composition in untrained women - S. Ellefsen; O. Vikmoen; G. Slettaløkken; J. E. Whist; H. Nygaard; I. Hollan; I. Rauk; G. Vegge; T. A. Strand; T. Raastad; B. R. Rønnestad (European Journal of Applied Physiology, 2014)

Mosquitoes rely on their gut microbiota for development - Kerri L. Coon; Kevin J. Vogel; Mark R. Brown; Michael R. Strand (Molecular Ecology, 2014)
Field studies indicate adult mosquitoes ( C ulicidae) host low diversity communities of bacteria that vary greatly among individuals and species. In contrast, it remains unclear how adult mosquitoes acquire their microbiome, what influences community structure, and whether the microbiome is important for survival. Here, we used pyrosequencing of 16S r RNA to characterize the bacterial communities of three mosquito species reared under identical conditions. Two of these species, A edes aegypti and A nopheles gambiae , are anautogenous and must blood‐feed to produce eggs, while one, G eorgecraigius atropalpus , is autogenous and produces eggs without blood feeding. Each mosquito species contained a low diversity community comprised primarily of aerobic bacteria acquired from the aquatic habitat in which larvae developed. Our results suggested that the communities in A e. aegypti and A n. gambiae larvae share more similarities with one another than with G . atropalpus . Studies with A e. aegypti also strongly suggested that adults transstadially acquired several members of the larval bacterial community, but only four genera of bacteria present in blood fed females were detected on eggs. Functional assays showed that axenic larvae of each species failed to develop beyond the first instar. Experiments with A e. aegypti indicated several members of the microbial community and E scherichia coli successfully colonized axenic larvae and rescued development. Overall, our results provide new insights about the acquisition and structure of bacterial communities in mosquitoes. They also indicate that three mosquito species spanning the breadth of the C ulicidae depend on their gut microbiome for development.

Seasonal variation in mineralization rates (C-N-P-Si) of mussel Mytilus edulis biodeposits - H. M. Jansen; M. C. J. Verdegem; Ø. Strand; A. C. Smaal (Marine Biology, 2012)

Oxidative stress protection and the repair response to hydrogen peroxide in the hyperthermophilic archaeon Pyrococcus furiosus and in related species - Kari R. Strand; Chengjun Sun; Ting Li; Francis E. Jenney; Gerrit J. Schut; Michael W. W. Adams (Archives of Microbiology, 2010)

Does increased abundance of sea lice influence survival of wild Atlantic salmon post‐smolt? - N. A. Hvidsten; B. Finstad; F. Kroglund; B. O. Johnsen; R. Strand; J. V. Arnekleiv; P. A. Bjørn (Journal of Fish Biology, 2007)
A synthesis of results from two projects was assessed to analyse possible influence of sea lice Lepeophtheirus salmonis on marine Atlantic salmon Salmo salar survival. During the years 1992–2004, trawling for wild migrating post‐smolts was performed in Trondheimsfjord, a fjord in which no Atlantic salmon aquaculture activity is permitted. Prevalence and intensity of sea lice infections on migrating wild post‐smolts differed between years. A correlation analysis between 1 sea‐winter (SW) Atlantic salmon catch statistics from the River Orkla (a Trondheimsfjord river) and sea lice infections on the migrating smolts in the Trondheimsfjord was not significant. Up to 2% reduction in adult returns due to sea‐lice infection was expected. In addition, experimental releases from 1996 to 1998 with individually tagged groups of hatchery‐reared Atlantic salmon smolts given protection against sea‐lice infection was performed. Higher recaptures of adult Atlantic salmon from 1998 treated smolts compared to the control group may correspond to high abundance of sea lice found on the wild smolt, and may indicate influence on post‐smolt mortality. These studies indicate that post‐smolt mortality in Trondheimsfjord is marginally influenced by sea lice infection; however, the methods for assessing wild smolt mortality might be insufficient. Higher infections of sea lice farther out in the fjord may indicate more loss in Atlantic salmon returns in some years.

Population structure in a critically endangered arctic fox population: does genetics matter? - L. DALÉN; K. KVALØY; J. D. C. LINNELL; B. ELMHAGEN; O. STRAND; M. TANNERFELDT; H. HENTTONEN; E. FUGLEI; A. LANDA; A. ANGERBJÖRN (Molecular Ecology, 2006)
The arctic fox ( Alopex lagopus ) in Scandinavia is classified as critically endangered after having gone through a severe decline in population size in the beginning of the 20th century, from which it has failed to recover despite more than 65 years of protection. Arctic foxes have a high dispersal rate and often disperse over long distances, suggesting that there was probably little population differentiation within Scandinavia prior to the bottleneck. It is, however, possible that the recent decline in population size has led to a decrease in dispersal and an increase in population fragmentation. To examine this, we used 10 microsatellite loci to analyse genetic variation in 150 arctic foxes from Scandinavia and Russia. The results showed that the arctic fox in Scandinavia presently is subdivided into four populations, and that the Kola Peninsula and northwest Russia together form a large fifth population. Current dispersal between the populations seemed to be very low, but genetic variation within them was relatively high. This and the relative F ST values among the populations are consistent with a model of recent fragmentation within Scandinavia. Since the amount of genetic variation is high within the populations, but the populations are small and isolated, demographic stochasticity seems to pose a higher threat to the populations’ persistence than inbreeding depression and low genetic variation.

The Lyngen Gabbro: the lower crust of an Ordovician Incipient Arc - Astri J. S. Kvassnes; Anita Hetland Strand; Heidi Moen-Eikeland; Rolf Birger Pedersen (Contributions to Mineralogy and Petrology, 2004)

Surrogate Pheromone Plumes in Three Forest Trunk Spaces: Composite Statistics and Case Studies - Harold W. Thistle; Holly Peterson; Gene Allwine; Brian Lamb; Tara Strand; Edward H. Holsten; Patrick J. Shea (Forest Science, 2004)
An atmospheric tracer gas was used as a pheromone surrogate to study near-field canopy dispersion within the trunk space. The objective is to improve guidance for forest managers deploying bark beetle antiaggregation pheromone sources to protect high-value forest stands. Data are shownfrom field studies in three forest canopies (oak-hickory, Quercus-Carya; lodgepole pine, Pinus contorta Dougl. ex Loud.; and ponderosa pine, Pinus ponderosa Dougl. ex Laws.) and include over 13,000 chemical tracer samples compiled into half-hour dispersion fields arounda point source. Maximum normalized concentrations (χ/Q) at each arc distance for each sampling period were of similar order at 5 m from the tracer source in the three canopies, although the differences in maximum χ/Q between canopies increased with distance from thesource. Plume dilution was highest in this study in the more open ponderosa pine canopy. A high-frequency tracer gas analyzer was also deployed to ascertain the structure of the gas plumes at 1 Hz. The high-frequency tracer data showed that the 30-minute average mean plumes are compositesof narrow filamentous plumes. The near-field plumes in each canopy were strongly affected by changes in atmospheric stability, as wander range and meander frequency increased after the morning transition to an unstable boundary layer. FOR. SCI. 50(5):610–625.

Estimating the patch size of larval fishes during colonization on coral reefs - D. Lecchini; V. Dufour; J. Carleton; S. Strand; R. Galzin (Journal of Fish Biology, 2004)
Fish larvae were sampled daily over a period of 14 days using six crest nets spaced at 200 m intervals on a coral reef on the west coast of Moorea Island, French Polynesia, to estimate the extent to which ichthyonekton arriving at one location reflected ichthyonekton arriving at neighbouring areas. Each night, the six crest nets were colonized by larval fishes from the same location.

Impaired larval development in broods of eelpout (Zoarces viviparus) in Danish coastal waters - J. Strand; L. Andersen; I. Dahllöf; B. Korsgaard (Fish Physiology and Biochemistry, 2004)

Integrating biodiversity priorities with conflicting socio-economic values in the Guinean–Congolian forest region - P.H. Williams; J.L. Moore; A. Kamden Toham; T.M. Brooks; H. Strand; J. D'Amico; M. Wisz; N.D. Burgess; A. Balmford; C. Rahbek (Biodiversity and Conservation, 2003)

Soil carbon stores in Nordic well‐drained forest soils—relationships with climate and texture class - I. CALLESEN; J. LISKI; K. RAULUND‐RASMUSSEN; M. T. OLSSON; L. TAU‐STRAND; L. VESTERDAL; C. J. WESTMAN (Global Change Biology, 2003)
Soil organic carbon (SOC) pools in forest floors and mineral soil to a depth of 100 cm were determined in 234 well‐drained Nordic forest soils from latitude 55–68???°‐N, and longitude 6–28???°‐E. The data were compiled in a database of Nordic forest soils, from literature, and sources of validated data the authors had access to. The SOC pool increased with both mean annual temperature (MAT) and mean annual precipitation (MAP), and the increase with MAT was more pronounced for coarse‐textured soils than for medium‐textured soils. Soil organic carbon in fine‐textured soils was not correlated with MAT and MAP. Differences between texture classes were mainly due to different carbon stores in the upper 40 cm of the mineral soil and in the forest floor. The emphasis on well‐drained soils eliminated the impact of hampered decomposition in hydromorphic soils. Large carbon accumulation in such soils probably explains the negative relationship between SOC and temperature reported in other studies. The increase in SOC with temperature and precipitation is interpreted as an indirect effect of higher net primary production.

High‐resolution determination of coral reef bottom cover from multispectral fluorescence laser line scan imagery - Charles H. Mazel; Michael P. Strand; Michael P. Lesser; Michael P. Crosby; Bryan Coles; Andrew J. Nevis (Limnology and Oceanography, 2003)
A prototype in‐water laser line‐scanning multispectral fluorescence imaging system was evaluated for its ability to provide data that could be used to determine the quantitative distribution and abundance of various functional groups on coral reefs. The system collected fluorescence imagery in three spectral bands with 1 cm 2 resolution at sites in Florida and the Bahamas. Fluorescence excitation was at 488 nm, and imagery was collected in emission bands centered at 520, 580, and 685 nm. Ground truth data on bottom cover was collected by divers using conventional line transect and photographic quadrat methods. A set of classification rules based on the relative signal levels in the three fluorescence channels was developed to assign the image pixels to functional groups. Once the image was classified, percent cover data for the groups were computed for the full image and for subsets of the image chosen to simulate line transect, grid survey, and photographic quadrat surveys. The statistics of percent cover of various bottom types derived from the fluorescence image compared favorably with those determined by diver survey techniques. The results demonstrate that fluorescence imaging has the long‐term potential to provide coverage of large spatial areas of coral reefs at high resolution, with automated classification and quantification of functional groups in the image.

Parallel climate model (PCM) control and transient simulations - W. M. Washington; J. W. Weatherly; G. A. Meehl; A. J. Semtner Jr.; T. W. Bettge; A. P. Craig; W. G. Strand Jr.; J. Arblaster; V. B. Wayland; R. James; Y. Zhang (Climate Dynamics, 2000)

Sea-ice effects on climate model sensitivity and low frequency variability - G. A. Meehl; J. M. Arblaster; W. G. Strand Jr (Climate Dynamics, 2000)

Synthesis of theoretical and empirical experiences from nutrient and cyprinid reductions in Lake Ringsjön - E. Bergman; L.-A. Hansson; A. Persson; J. Strand; P. Romare; M. Enell; W. Granéli; J. M. Svensson; S. F. Hamrin; G. Cronberg; G. Andersson; E. Bergstrand (Hydrobiologia, 1999)

Evaluation of several degree-day estimation methods in California climates - William J. Roltsch; Frank G. Zalom; Ann J. Strawn; Joyce F. Strand; Michael J. Pitcairn (International Journal of Biometeorology, 1999)

Constrained oviposition and female-biased sex allocation in a parasitic wasp - P. J. Ode; Michael F. Antolin; Michael R. Strand (Oecologia, 1997)

Nuclear DNA‐based markers for plant evolutionary biology - A. E. Strand; J Leebens‐Mack; B. G. Milligan (Molecular Ecology, 1997)
While DNA‐based markers can provide a wealth of information for the study of plant evolutionary biology, progress is limited by the lack of primers available for PCR. To overcome this limitation, we outline a protocol for developing oligonucleotide primers targeting regions of low copy‐number nuclear genes. This protocol is intended to lead to universally useful primer sets. To test our approach, we designed eight primer sets and tested their abilities to amplify targets from representatives of each dicot and one monocot subclass. Five of the eight primer sets amplified targets from at least five of the seven taxa and thus exhibited broad taxonomic usefulness; the remaining primers were rather specific, however, and amplified targets from at most three taxa. In only one primer‐taxon combination was a complex multiple‐banded amplification produced. Overall, the protocol outlined proved quite useful at identifying broadly applicable primers targeted to low copy‐number nuclear genes. Wider application of this approach should be effective at greatly increasing the amount of genetic information available for a diversity of plant nuclear genomes.

Superparasitism and ovicide in parasitic Hymenoptera: theory and a case study of the ectoparasitoid Bracon hebetor - M. R. Strand; H. C. J. Godfray (Behavioral Ecology and Sociobiology, 1989)

Oxygen and nitrate reduction kinetics of a nonflocculating strain of Zoogloea ramigera - S. E. Strand; A. J. McDonnell; R. F. Unz (Antonie van Leeuwenhoek, 1988)

Sectional notes - Carl H. Metzger; W. B. Ward; H. L. Cochran; J. B. R. Dickey; A. B. Strand; W. H. Friend; H. H. Zimmerley; G. S. Ralston (American Journal of Potato Research, 1939)